2019
DOI: 10.22502/jlmc.v7i1.280
|View full text |Cite
|
Sign up to set email alerts
|

Drug Utilization Pattern by Using WHO Core Prescribing Indicators in Orthopedics and Obstetrics / Gynecology Departments of a Tertiary Care Hospital

Abstract: Introduction: Drug utilization research is an important tool to facilitate rational use of drugs. In low income countries irrational use of drugs is a common problem like overuse of drugs and inappropriate use of antibiotics, leading to poor treatment outcome and increased burden of treatment. This study was conducted to provide understanding of drug utilization pattern by using WHO Core Prescribing Indicator. Methods: This study was conducted in Orthopedics and Obstetrics / Gynecology departments. Patients vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
3
8
0
Order By: Relevance
“…The rate of drugs from essential drug list in our study was 33.8% which was quite low than the expected WHO value (100%) [7] and was found to be significantly lower in young adults compared to elderly (p=0.038). Our result is consistent with those reported by Karki et al [16] who found that 34.3% of drugs were prescribed from essential drug list at the orthopedics department. In a recent study, which evaluated the rational drug use at the obesity outpatient clinic of a tertiary care hospital in Turkey, higher percentages of drugs prescribed from essential drug list were found (61.4%).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The rate of drugs from essential drug list in our study was 33.8% which was quite low than the expected WHO value (100%) [7] and was found to be significantly lower in young adults compared to elderly (p=0.038). Our result is consistent with those reported by Karki et al [16] who found that 34.3% of drugs were prescribed from essential drug list at the orthopedics department. In a recent study, which evaluated the rational drug use at the obesity outpatient clinic of a tertiary care hospital in Turkey, higher percentages of drugs prescribed from essential drug list were found (61.4%).…”
Section: Discussionsupporting
confidence: 93%
“…Unlike our findings, two studies reported acute trauma and fractures as the most common diagnoses at the orthopedic departments. [15,16] Non-steroidal anti-inflammatory drugs (NSAIDs) are frequently used drugs for the management of musculoskeletal conditions. [17] Gastroprotective agents are commonly prescribed concomitantly with NSAIDs to reduce the adverse effects (gastrointestinal ulcers, bleeding), morbidity and mortality due to NSAIDs long-term use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, the average number of drugs per patient, that is an important prescribing indicator evaluating rational drug use, was 2.9 which is higher than the WHO ideal values (1.6-1.8). Our finding was similar to those reported by Kumar et al and Karki et al (3 and 2.9, respectively), 19,20 . The most commonly prescribed drugs in this study were NSAIDs, PPIs and skeletal muscle relaxants (Figure 1).…”
Section: Discussionsupporting
confidence: 93%